APHORISMS IN ENGLISH AND UZBEK, EXPRESSING LOVE FOR MOTHER - Jo’raqulova Hurmatoy, (TADQIQOTLAR, 2025)
Annotation:  This  article  explores  the  thematic  and  cultural  significance  of aphorisms  that  express  motherly  love  in  Uzbek  and  English  traditions.  Using  a comparative literary approach, the study analyzes selected aphorisms, proverbs, and quotations from both cultures. The findings reveal that maternal love is universally portrayed  as  unconditional,  eternal,  and  protective.  However,  Uzbek  aphorisms emphasize the sacred and spiritual role of the mother, often linking her blessing to divine approval, while English aphorisms highlight her emotional and motivational influence  on  personal  growth  and  achievement.  The  article  concludes  that,  despite cultural variations, the image of the mother remains a timeless symbol of compassion, sacrifice, and guidance in human life.